Photoinduced Formation of an Azobenzene‐Based CD‐Active Supramolecular Cyclic Dimer1. Issue 18 (12th March 2015) - Sogawa, Hiromitsu; Terada, Kayo; Miyagi, Yu; Shiotsuki, Masashi; Inai, Yoshihito; Masuda, Toshio; Sanda, Fumio
Abstract A series of new photo‐responsive amino acid‐derived azobenzenedicarboxylic acid derivatives (S)‐1 a–e were synthesized. Compound (S)‐1 a in the trans form exhibited no circular dichroism (CD) signal in DMF under ambient conditions, whereas intense Cotton effects were observed upon UV irradiation, indicating the formation of a chiral supramolecular structure in the cis form. The CD signals disappeared when trifluoroacetic acid (TFA) was added to the solution. The ester counterpart [(S)‐1 a′] showed no CD signal. Hydrogen bonding between the carboxy groups seemed necessary for constructing the supramolecular structure. The kinetic studies of cis to trans isomerization of (S)‐1 a demonstrated that the formation of a chiral supramolecule enhances the stability of the cis‐azobenzene structure. The ESI mass spectrum of stilbenedicarboxylic acid (S)‐4, an analogue of (S)‐1 b, confirmed the formation of a dimer. A theoretical CD study revealed that (S)‐1 a in the cis form should be present as a cyclic chiral dimer.